2017
DOI: 10.1002/adsc.201700134
|View full text |Cite
|
Sign up to set email alerts
|

Amine Activation: N‐Arylamino Acid Amide Synthesis from Isothioureas and Amino Acids

Abstract: N-arylamino acid amides have been synthesized via a novel method based on N-arylamine activation into isothioureas followed by reaction with amino acids under iron catalysis. The activated N-arylamines are easily prepared using a three-component reaction with commercial reagents, tert-butylisocyanide and S-phenyl benzenethiosulfonate. The protocol shows a broad functional group compatibility, with respect to side chain functionality of the amino acid (e. g. aliphatic and aromatic OH, (hetero)aromatic NH, amide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 87 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…Amide, as one of the crucial active motifs in organic synthesis, ubiquitously exists in a large number of bioactive molecules, such as herbicidal, bactericidal, antiviral, and insecticidal molecules. , For a specific example in 2013, the methyl thiazide bearing an amide unit, as a plant activator, can be applied in many cash crops such as tobacco, rice, and cucumber to mainly control viral diseases including TMV . Notably, among the amide derivatives, α-ketoamide is a considerably special amide derivative, which not only has excellent biological activity, existing in many natural products, polypeptides, , and many biologically active molecules, , but also serves as a precursor for a variety of transformations in the chemical synthesis. , Interestingly, our previous work has indicated that a series of synthesized α-ketoamide derivatives exhibited good anti-TMV activities for potential use in plant protection, which is rarely reported in the pesticide area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amide, as one of the crucial active motifs in organic synthesis, ubiquitously exists in a large number of bioactive molecules, such as herbicidal, bactericidal, antiviral, and insecticidal molecules. , For a specific example in 2013, the methyl thiazide bearing an amide unit, as a plant activator, can be applied in many cash crops such as tobacco, rice, and cucumber to mainly control viral diseases including TMV . Notably, among the amide derivatives, α-ketoamide is a considerably special amide derivative, which not only has excellent biological activity, existing in many natural products, polypeptides, , and many biologically active molecules, , but also serves as a precursor for a variety of transformations in the chemical synthesis. , Interestingly, our previous work has indicated that a series of synthesized α-ketoamide derivatives exhibited good anti-TMV activities for potential use in plant protection, which is rarely reported in the pesticide area.…”
Section: Introductionmentioning
confidence: 99%
“…Amide, as one of the crucial active motifs in organic synthesis, ubiquitously exists in a large number of bioactive molecules, 21 such as herbicidal, 22 bactericidal, 23 antiviral, 24 and insecticidal molecules. 25,26 For a specific example in 2013, the methyl thiazide bearing an amide unit, as a plant activator, can be applied in many cash crops such as tobacco, rice, and cucumber to mainly control viral diseases including TMV.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Over the past years, amide derivatives have received much attention owing to their broad range of applications in many fields such as the pharmaceutical industry, chemical biology, the agrochemical industry, engineering plastics, and so on [ 1 , 2 , 3 , 4 , 5 , 6 ]. Various approaches have been developed for the synthesis of amide compounds including nucleophilic acyl substitution reactions with amines [ 7 ], Staudinger ligation [ 8 ], Schmidt reaction [ 9 ] and Beckmann rearrangement [ 10 ]. However, generations of large amounts of undesired by-products and corrosive phenomenon associated with common acid (H 2 SO 4 and SOCl 2 ) based on liquid phase protocols provide a challenging task for chemists to develop alternative methods [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, activation of amines, a reversal of the widely used carboxylic acid activation strategy, has emerged as a potentially important pathway for the construction of an amide bond since this procedure employs commonly available carboxylic acids and preactivated amines (Scheme B). Recognizing that N -activation strategies can greatly promote both catalytic C–H amination and amide bond formation, we hypothesized that a single nitrogen atom could be associated with two different activating groups, one to promote the aryl C–H amination and the other to facilitate the transformation to an amide functionality (Scheme C). If such a method is successful, it will construct both aryl and amidyl C–N bonds without oxidants or coupling reagents in a straightforward manner.…”
mentioning
confidence: 99%
“…The reactions would likely encounter chemoselectivity issues due to the competitive reactions between the two activating groups. The selection of the activation groups is difficult in view of the fact that only a few activated amines such as N -(imidazolyl­carbonyl)­amine, isocyanide, iminophosphorane (in situ), and isothiourea were used in amide formation, and the sulfonyl group often used as a protecting group in catalytic C–H amination was removed generally under harsh reaction conditions. , …”
mentioning
confidence: 99%